STUDY ON THE RELATIONSHIP BETWEEN PEOPLE'S PERSONAL SATISFACTION AND THEIR AGE - Clemente Carrión, Antonio; Molero Mañes, Rosa Josefa; González Sala, Francisco (Anales de Psicología / Annals of Psychology, 2000)
In this article we shall analyze the relationship between people's age and their level of personal happiness or satisfaction. This study is based on a sample of people of both sexes between the ages of 18 and 65. The results obtained from the Analyses of Variance prove that the rate of satisfaction diminishes as one gets older.